2021
DOI: 10.5312/wjo.v12.i4.214
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of porous titanium and tantalum implants in ovariectomized rabbits: A biomechanical study

Abstract: BACKGROUND Today, biological fixation of uncemented press-fit acetabular components plays an important role in total hip arthroplasty. Long-term stable fixation of these implants depends on the osseointegration of the acetabular cup bone tissue into the acetabular cup implant, and their ability to withstand functional loads. AIM To compare the strength of bone-implant osseointegration of four types of porous metal implants in normal and osteoporotic bone in rabbits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Contrastingly, Wu et al performed a pull-out test, with five PTi alloy structures with varying porosity levels, and found that the PTi cages with the two highest porosity levels demonstrated statistically significantly higher pull-out strengths than the PTa cage [11]. Bondarenko et al performed a test of implant break-out force, comparing the force required to detach an implant from both normal and osteoporotic bone tissue 8 weeks after implantation in four available PTi alloy implants against the PTa implant [2]. They found that in both normal and simulated osteoporotic bone, the breakout force of the tantalum was not significantly different than two of the three titanium alloy products, but one of the titanium alloy products withstood much lower break-out force than the other three [2].…”
Section: Mechanical Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrastingly, Wu et al performed a pull-out test, with five PTi alloy structures with varying porosity levels, and found that the PTi cages with the two highest porosity levels demonstrated statistically significantly higher pull-out strengths than the PTa cage [11]. Bondarenko et al performed a test of implant break-out force, comparing the force required to detach an implant from both normal and osteoporotic bone tissue 8 weeks after implantation in four available PTi alloy implants against the PTa implant [2]. They found that in both normal and simulated osteoporotic bone, the breakout force of the tantalum was not significantly different than two of the three titanium alloy products, but one of the titanium alloy products withstood much lower break-out force than the other three [2].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Bondarenko et al performed a test of implant break-out force, comparing the force required to detach an implant from both normal and osteoporotic bone tissue 8 weeks after implantation in four available PTi alloy implants against the PTa implant [2]. They found that in both normal and simulated osteoporotic bone, the breakout force of the tantalum was not significantly different than two of the three titanium alloy products, but one of the titanium alloy products withstood much lower break-out force than the other three [2]. In a unique test that sought to compare the compression deformation resistance and stress-strain parameters of both scaffold types with that of pig bone, Fan et al performed uniaxial compression tests on the scaffolds and found that the deformation behaviour and stress-strain parameters of the tantalum scaffolds were closer to that of pig bone scaffolds than the titanium scaffolds [12].…”
Section: Mechanical Testingmentioning
confidence: 99%
See 2 more Smart Citations